1981
DOI: 10.1111/j.1539-6924.1981.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Components of Risk Ratings

Abstract: This study examined what lay people mean when they judge the "risk" of activities that involve the potential for accidental fatalities (e.g., hang gliding, living near a nuclear reactor). A sample of German and American students rated the "overall risk" of 14 such activities and provided 3 fatality estimates: the number of fatalities in an "average year," the individual yearly fkality probability (or odds), and the number of fatalities in a "disastrous accident." Subjects' fatality estimates were reasonably ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…flooding, Tsunami), Japanese people's risk perception is weakened as their distance from the risk source increases. This finding supports previous research (Sjoberg, 2000;von Winterfeldt, John & Borcherding, 1981;Lichtenstein et al, 1978) that real risk does affect risk perception, however, the mixed results from the three countries imply that real risks are not always correctly perceived, this is also confirmed by other papers (Brody, Peck & Highfield, 2004). Some reasons may account for this difference in the capability of risk judgment: First, based on the results of this paper, a country's economic development is one factor that correlates with public risk perception, even though it is not necessarily to be a causal relationship.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…flooding, Tsunami), Japanese people's risk perception is weakened as their distance from the risk source increases. This finding supports previous research (Sjoberg, 2000;von Winterfeldt, John & Borcherding, 1981;Lichtenstein et al, 1978) that real risk does affect risk perception, however, the mixed results from the three countries imply that real risks are not always correctly perceived, this is also confirmed by other papers (Brody, Peck & Highfield, 2004). Some reasons may account for this difference in the capability of risk judgment: First, based on the results of this paper, a country's economic development is one factor that correlates with public risk perception, even though it is not necessarily to be a causal relationship.…”
Section: Discussionsupporting
confidence: 83%
“…The beginning of risk perception research can be traced to the nuclear debate of the 1960s, yet today it still remains as a phenomenon in search of an explanation (Sjoberg, 2000). Of course, real risk is undoubtedly a primary factor that affects risk perception, as illustrated by some well sited papers (von Winterfeldt, John & Borcherding, 1981;Lichtenstein et al, 1978). However, numerous empirical studies have reported that risk is perceived quite differently even in the case where the statistical probability of a certain risk is identical.…”
Section: Introductionmentioning
confidence: 99%
“…In psychology, research within what has been called the "psychometric paradigm" has explored the ability of psychophysical scaling methods and multivariate analysis to produce meaningful representations of risk attitudes and perceptions (see, for example, Gardner et al, 1982;Green, 1980;Green & Brown, Renn, 1981;Slavic, Fischhoff, & Lichtenstein, 1980bVlek & Stallen, 1981;von Winterfeldt et al, 1981).…”
Section: The Psychometric Paradigmmentioning
confidence: 99%
“…power, genetic engineering) are subject to an intense public debate, the Slovic, Fischhoff & Lichtenstein, 1980Rowe, 1977;Schwing & Albers, 1980;Starr, 1969;von Winterfeldt, John & Borcherding, 1981). A significant part of this research has been devoted to the construction of multivariate representations of risks based upon the judgments of experts and lay people.…”
Section: Risk Representationsmentioning
confidence: 99%